2020
DOI: 10.1002/mp.14432
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the thermal sensitivity of porcine liver in CT‐guided cryoablation: an initial study

Abstract: Purpose: To evaluate computed tomography (CT)-based thermometry in cryoablation, the thermal sensitivity of an ex-vivo porcine liver was determined in an initial study design. Methods: The CT-guided cryoablation was performed in three porcine liver samples over a period of 10 min. Fiber optic temperature probes were positioned parallel to the shaft of the cryoprobe in an axial slice orientation. During ablation, temperature measurements were performed simultaneously with CT imaging at 5 s intervals. On the CT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…It is not unknown that there is a correlation between temperature and CT attenuation of hepatic tissue. Using a similar experimental setup, Huebner et al reported a thermal sensitivity of 0.95 HU / °C ( R 2 = 0.73) in an ex vivo porcine liver model [ 15 ]. Pohlan et al reported a thermal sensitivity of even 2.11 HU / °C ( R 2 = 0.55) using porcine liver placed on porcine ribs [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not unknown that there is a correlation between temperature and CT attenuation of hepatic tissue. Using a similar experimental setup, Huebner et al reported a thermal sensitivity of 0.95 HU / °C ( R 2 = 0.73) in an ex vivo porcine liver model [ 15 ]. Pohlan et al reported a thermal sensitivity of even 2.11 HU / °C ( R 2 = 0.55) using porcine liver placed on porcine ribs [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…An explanation for the observed deviations might be that Huebner et al used temperatures as low as − 75.4 °C compared to − 41.1 °C in our study and about − 35 °C in Pohlan et al Due to the plateau below − 20 °C, which can also be observed in the study of Huebner et al, the influence of even lower temperatures will most likely attribute to a flattening of the correlation line translating into a reduction thermal sensitivity. Additionally, we used a reference tube voltage of 70 kVp compared to 120 kVp of Huebner et al and Pohlan et al [ 11 , 15 ]. Due to the stagnating CT-values at temperatures below − 20 °C, we decided to separately assess the thermal sensitivity of this range of transition, where we calculated a significantly higher value of 2.2 HU / °C ( R 2 = 0.40) at 120 keV VMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ablation was performed at 20 W. Over a period of 16 min, ablation was performed intermittently for 25 s, followed by an interruption of 5 s to perform MR thermometry. Using proton resonance frequency (PRF) thermometry, temperatures were calculated over an ROI of 2 × 2 pixels [23,24]. A comparison of the measured and calculated temperature values showed a slope of m = 1.06 and a correlation coefficient of 1.…”
Section: Mri-compatibility and Thermometrymentioning
confidence: 99%
“…However, to date the clinical requirements for intraprocedural temperature mapping-specifically the combination of 1-2 mm spatial resolution, <5 °C temperature accuracy and clinically acceptable radiation dose-have been very challenging to achieve. Recent advances in spectral CT, combined with the introduction of advanced reconstruction and postprocessing algorithms to reduce noise without sacrificing quantitative accuracy, offer the opportunity to break this barrier and have renewed the interest in CT-based thermometry for clinical applications (Hübner et al 2020, Heinrich et al 2022, Shapira et al 2022, Liu et al 2023, Wang et al 2023.…”
Section: Introductionmentioning
confidence: 99%